(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article notes that insurance is an integral part of the financial infrastructure a market economy and an important factor in ensuring the sustainable development of the economy as a whole and the role of the insurance in ensuring the continuity of production and protection of the population from accidents in a market economy. In particular, the current state of life insurance in Uzbekistan was analyzed and suggestions and conclusions were made on the direction of development.